2020
DOI: 10.1007/s10840-020-00810-1
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for subcutaneous implantable cardioverter-defibrillator in patients with left ventricular assist device

Abstract: Purpose The subcutaneous implantable cardioverter-defibrillator (S-ICD) could be a promising alternative to the conventional transvenous ICD in patients with LVAD due to its reduced risk of infection. However, surface ECG is altered following LVAD implantation and, since S-ICD detection is based on surface ECG, S-ICD could be potentially affected. The aim of the present study was to analyze S-ICD eligibility in patients with LVAD. Methods Seventy-five patients implanted with an LVAD were included in this prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…With the ECG-based screening test higher eligibility rates (66.6%), similar to those found in the present study, were observed. 7 Thus, S-ICD eligibility in patients with LVAD is lower in comparison to patients with heart failure without an LVAD. 17,18 In the present study, 66 patients (57%) were found eligible for…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With the ECG-based screening test higher eligibility rates (66.6%), similar to those found in the present study, were observed. 7 Thus, S-ICD eligibility in patients with LVAD is lower in comparison to patients with heart failure without an LVAD. 17,18 In the present study, 66 patients (57%) were found eligible for…”
Section: Discussionmentioning
confidence: 99%
“…Conventional limb electrodes (LA, RA, LL) were placed according to manufacturer recommendations as described elsewhere (Figure 2B). 7 These simulated S‐ICD vectors were obtained at gains of 5, 10, and 20 mV/cm at a paper speed of 25 mm/s using an ECG device (MAC 5500; GE Healthcare) in supine and erect position. S‐ICD eligibility was evaluated in both left and right parasternal position.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations